Partisipasi Masyarakat dalam Pengembangan Ekowisata di Pangandaran-Jawa Barat - Sri Hayati (Forum Geografi, 2010)
Pangandaran is one of tourist destination which located on the south coast of West Java, administratively belongs to the Ciamis district. This area covers about 5000 hectares with a total of 6670 households spread over top uniting Tombolo Pananjung forest national park with the island of Java. Ecotourism is developed here as an effort to give more attention to conservation and local development. This study aims to determine strength of relationship between public perception of public attitudes towards ecotourism and environmental tourism with community participation in ecotourism development. This study population is preserved at the age of productive society. Taking a sample of 200 respondents conducted randomly. Data were collected through questionnaire-shaped instrument. Data analysis by using inferential statistics is a simple correlation, multiple, and partial. Results showed that there was a significant relationship between public perception of public attitudes towards ecotourism and environmental tourism with public perception in the development of both simple and double ecotourism. Each simple correlation 0.59 (p